2019
DOI: 10.1055/a-0905-3173
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal tunneling endoscopic resection of large submucosal tumors originating from the muscularis propria layer in the esophagus and gastric cardia

Abstract: Aims The aim of this study was to evaluate the short-term complications of submucosal tunneling endoscopic resection (STER) for large submucosal tumors (SMTs) originating from the muscularis propria (MP) layer in the esophagus and gastric cardia. Methods We performed 286 cases of STER from September 2012 to December 2017. The clinical data of patients with SMTs originating from the MP layer of 3.0–7.0 cm, who underwent STER procedure at the endoscopy center of Tianjin Medical University General Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
2
1
3
Order By: Relevance
“…In this study, we found that the procedure duration of mark-guided STER was shorter compared with several previous studies, whereas the en bloc resection rate of mark-guided STER was prominently higher than that of these studies [ 15 , 16 , 21 ]. However, multivariate logistic regression demonstrated that procedure duration was an independent factor associated with en bloc resection.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this study, we found that the procedure duration of mark-guided STER was shorter compared with several previous studies, whereas the en bloc resection rate of mark-guided STER was prominently higher than that of these studies [ 15 , 16 , 21 ]. However, multivariate logistic regression demonstrated that procedure duration was an independent factor associated with en bloc resection.…”
Section: Discussioncontrasting
confidence: 53%
“…Wang et al have evaluated the feasibility and safety of STER for the treatment of large esophageal SMTs (ranging from 30 mm to 70 mm) originating from the MP layer and demonstrated that complete resection, en bloc resection, and adverse events rates are 100%, 85.2%, and 14.8%, respectively [ 21 ]. Chen et al have shown that the en bloc resection and adverse event rates are 84.6% and 7.7%, respectively, when large esophageal SMTs (˃50 mm) originating from the MP layer are removed by STER [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Не смотря на существующие ограничения [13,[18][19][20] в эндоскопических вмешательствах при размерах опухолей более 30 мм из-за сложности их извлечения, описаны случаи эндоскопического удаления опухолей размером более 3,5 см с возможной фрагментацией новообразования и извлечением фрагментов [21][22][23][24][25][26][27], что подтверждается полученными нами данными.…”
Section: Discussionunclassified
“…Опухоли, локализующиеся глубоко в стенке пищевода и исходящие из его собственного мышечного слоя, характеризовались, как правило, несколько большими размерами и удалялись методом туннельной диссекции (13 случаев). Расположенные в подслизистом слое (1), исходящие и локализующиеся в пределах мышечной пластинки слизистой оболочки (8) СЭО удалены методом резекции слизистой оболочки (2) и диссекции в подслизистом слое пищевода (7). У двух пациентов с СЭО нижней трети пищевода на границе с пищеводно-желудочным переходом и тенденцией к внепросветному направлению роста интраоперационно возникли затруднения с визуальной оценкой локализации новообразований, что потребовало интраоперационного выполнения навигационной ЭУСр: уточнена позиция опухолей, в соответствии с ней определено положение оперативного доступа.…”
Section: результатыunclassified
“…Благодаря распространению современных методов диагностики СЭО пищевода все чаще встречаются в клинической практике, однако тактические вопросы их диагностики, наблюдения и удаления остаются дискутабельными [1][2][3]. Внедрение новых методик пероральной интервенционной гибкой эндоскопии позволяет эффективно и малоинвазивно удалять СЭО пищевода, выбирая метод в соответствии с уточненными характеристиками новообразований [1,4,5,7]. Таким образом, накопление и анализ клинического опыта диагностики и лечения СЭО пищевода не теряют актуальности.…”
Section: Introductionunclassified